2007
DOI: 10.1007/s11746-007-1053-5
|View full text |Cite
|
Sign up to set email alerts
|

Industrially Produced trans Fat in Foods in Australia

Abstract: Selected foods sampled from Australian supermarkets and fast food outlets were analyzed for trans fat (TF) content. The product with the highest amount of TF (6.3 g/100 g product) was a household shortening. The TF contents in spreads were remarkably low (average 0.5, range 0.2-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…In this study, a similar result was observed for maximum level (46.57 g/100 g fatty acids) of SFA in potato crisps. But minimum level in our study (27.98 g/100 g fatty acids) was higher than in Wijesundera et al [25] in potato crisps. In our study, the mean values of SFAs were determined to be 42.86, 40.78, 41.50, 44.97, 39.83, and 41.91 g/100 g fatty acids in cocoa cakes, mosaic cakes, chocolate cakes, cream cakes, hazelnut-cocoa cakes, and fruity cakes, respectively.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…In this study, a similar result was observed for maximum level (46.57 g/100 g fatty acids) of SFA in potato crisps. But minimum level in our study (27.98 g/100 g fatty acids) was higher than in Wijesundera et al [25] in potato crisps. In our study, the mean values of SFAs were determined to be 42.86, 40.78, 41.50, 44.97, 39.83, and 41.91 g/100 g fatty acids in cocoa cakes, mosaic cakes, chocolate cakes, cream cakes, hazelnut-cocoa cakes, and fruity cakes, respectively.…”
Section: Resultscontrasting
confidence: 86%
“…In comparison to our study, the low level SFA was observed in other studies of potato crisps. [22,24] Wijesundera et al [25] found that SFA ranged from 7.9 to 46.7 g/100 g fat in potato chips. In this study, a similar result was observed for maximum level (46.57 g/100 g fatty acids) of SFA in potato crisps.…”
Section: Resultsmentioning
confidence: 99%
“…2003), Costa Rica (palm shortening, average 1.30%) (Baylin et al. 2007) and Australia (household shortening, 1.7–6.3%) (Wijesundera et al. 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It then became mandatory to declare TFA content exceeding 0.5 g/serving on the product label. While no product is prohibited from sale on the basis of TFA content in the U.S.A., Denmark has prohibited the use of oils and fats containing more that 2.0 g TFA/100 g fat (Wijesundera et al. 2007).…”
Section: Resultsmentioning
confidence: 99%
“…With hindsight, the approach may have proved adequate in Australia and New Zealand because the analysed composition of manufactured foods showed a narrow range of TFA content of foods; up to five brands of the same food were analysed to obtain a range (Wijesundera et al, 2007). In countries, for example, Canada (Health Canada, 2006), where the use of partially hydrogenated fats with very high TFA content may be more common, the range of TFA content of foods is likely to be much higher and the population estimate of TFA intake using this approach less reliable.…”
Section: Per Capita Food Consumptionmentioning
confidence: 99%